PEMBINAAN IBU RUMAH TANGGA MELALUI JUAL BELI SECARA E-COMMERCE DI PERUMAHAN CITRA LAGUNA - Tiurniari Purba; Irene Svinarky (PUAN INDONESIA, 2022)
Community Service (PKM) aims to foster housewives in Citra Laguna Housing, Batam. More than 50 percent of the housewives in this housing simply carry out the profession as a housewife without any other activities. Meanwhile, complaints about the inadequacy of household needs are very high. They want extra money to make ends meet. Through this PKM, the implementation method forms direct training and practice on making homemade ice cream products and selling them online or e-commerce. Implementation is carried out twice per meeting. First, fostering participants and practice on how to make ice cream, which was represented by 15 participants. Second, teach and practice buying and selling online through internet media such as through Facebook, Instagram, and others (e-commerce which is familiar among housewives). The results during the two meetings are as follows: 1. Housewives mastered how to make ice cream products with satisfactory results. 2. Housewives know how to download images of products they want to sell in common marketing languages.